Kondisi Data Geospasial dalam Mendukung Pelayanan Pajak Bumi dan Bangunan - Santosa, Purnama Budi; Subaryono, Subaryono; Diyono, Diyono; Pamungkas, Sidik Dwi (2016)
Tax is one of important sources of nations’ revenue that is essential for prosperity and welfare of the community. One type of taxes which is potential to be the source of revenue is Land and Building Tax (PBB). According to the Act No. 28 year 2009 on Regional Taxes and Levies (PDRD), as has been approved on 15th September 2009, the Land and Building Tax for Urban Rural Sector (PBB-P2) which was originally managed by central government was transferred to local taxes and are managed entirely in local governments. In response to this, some local governments have appointed DISPENDA dan DPPKAD to regulate and manage the PBB. However, it is found that some DISPENDA and DPPKAD are not ready to handle the PBB due to some reasons. One noticeable reason is the lack of availability and quality of geopastial data. With this condition, the local governments will not be able to manage the up-to-date tax value of the PBB precisely and accurately. Therefore this research was conducted to evaluate the quality of geospatial data at local governments. The Evaluation was conducted by comparing the PBB’s block maps with the surveyed data by using GPS RTK-NTRIP. The evaluation is focused on the aspects of geometry and position. Furthermore, questionaires and interviews were also conducted to measure the local government afficers’ perception about their condition, and to evaluate the existing codition. The results show that in term of geospatial data quality elements, 56,52% of the sample data show accurate position. Meanwhile, 49,9% of the sample data presents complete tax object attribute elements. However, in term of the SDI’s geospatial data component, it is found that most the local governments do not have sufficient quality geospatial data.